Open-sourcing French culture: The politics of métissage and collective reappropriation in the films of Abdellatif Kechiche. (28th October 2011) - Williams, James S.
This article examines in detail the intertextual sources and transcultural strategies of Abdellatif Kechiche's first three films: La Faute à Voltaire/Blame it on Voltaire (2000), L'Esquive/Games of Love and Chance (2003), and La Graine et le mulet/Couscous (2007). It assesses to what degree Kechiche subverts the cultural and symbolic frame politically within the lived context of multi-ethnic France, or simply re-stages the diasporic experience within a syncretic yet politically complacent conceptual frame based around a cultural memory that is almost exclusively French and gestures consistently towards the universal. By tracing each film's construction of a particular social-cultural frame that actively draws on the symbolic framework of State and Nation, this article reveals how Kechiche's work of alterity serves to reappropriate and recontextualize key signifiers of French culture by placing them in new, progressive and necessarily 'impure' allegorical and symbolic frameworks that operate beyond fixed, essentialist notions of identity (subjective, familial, social, ethnic). Moreover, Kechiche's cinema 'de-frames' itself by foregrounding the performative aspects of cultural métissage, illustrating in the process that personal identity and development is always 'performed' in collective solidarity with others. For these reasons, Kechiche's 'acts' of cinematic form may best be conceived as radical 'social acts' that herald a new form of transcultural 'opensourcing', i.e. a programme of open access and redistribution of French culture that offers up a set of important source codes and texts and positively invites creative modification and reinvention. Such a radical practice of social and cultural mixité demands, ultimately, that we respond in kind by grasping its multiple strands and working together to create new and as yet unimagined social and cultural formations.